Department of the Air Force Family Advocacy Program: Exploring the Impact of an Antiviolence Intervention Program for Women - Larance, Lisa Young (Violence against women, 2025)
This mixed-methods study explores the impact of the Vista curriculum, a trauma-informed antiviolence intervention program for women who have used force in their intimate relationships, delivered by the Department of the Air Force Family Advocacy Program clinicians. Questions sought to understand any changes in personal growth, self-awareness, beliefs, and relationship interaction skills for 62 cisgender women. Findings suggest that women gained personal growth, self-awareness, and increased relationship tools. Women identified the positive impact cofacilitator support and non-judgment had on them and their ability to heal from their experiences and increase their awareness of viable non-forceful alternatives. Policy and practice implications are discussed.